On the Matter of Competency Evaluation of the Experts from Budget Committees - Lambovska, Maya (Research Papers, 2005)
Aim of the paper is to work out a methodology for competency evaluation of experts from budget committees of large organization under conditions of uncertainty and lack of enough historical information.Paper consists of four parts. Prerequisites for working out the paper are set out in the first part. In the second part instruments of the methods from the third part are described. Third part contains six version methods for competency evaluation of experts from budget committees of the organization. In the fourth part effects of the methods’ applying are systematized and approbated.According to its author the paper could be qualified as a basic scientific elaboration on evaluation of experts from budget committees of the organization under uncertainty. IN a practical manner paper would support introducing of budgeting process into management practice of the organizations.